HUBUNGAN KEPEDULIAN ORANGTUA TERHADAP KEDISPLINAN BELAJAR SISWA SMP NEGERI 1 FANAYAMA TAHUN PELAJARAN 2021/2022 - Laila, Baziduhu (Jurnal Ilmiah Aquinas, 2022)
This study aims to describe the relationship between parental care and discipline in student learning SMP Negeri 1 Fanayama, South Nias Regency, in the 2021/2022 academic year. The results of the questionnaire validity test showed that all questions about parental care (variable X) and questions about student learning discipline (variable Y) were declared valid. Calculation of reliability for the variable X with a value of r11 = 0.951, is known the value of r11 > rtable so that the parental concern questionnaire is declared reliable. Calculation of reliability for the variable Y obtained with a value of r11 = 0.942 is classified as very high criteria. It can be concluded that the value obtained is r11>rtable so that the student learning discipline questionnaire is declared reliable. The results of the calculation between the variable X (parental concern) with the variable Y (student learning discipline) obtained a value rxy = 0.900. The rxy value was then consulted at r table = 0.900 for N = 20 at a significant level of 95%. Based on the results of the consultation, it is known that rxy > rtable, so in this case that there is a relationship between parental care and student discipline SMP Negeri 1 Fanayama. The results of the calculation the hypothesis test obtained the price of t = 8.752. while the t table price a significant level of 95% and dk = 20-2 = 18, then it is obtained that t table = 2.101, it turns out that the value of t count = 8.752 > t table so that Ho is rejected. it can be concluded that there is a relationship between parental care and student learning discipline.